2010
DOI: 10.1208/s12249-010-9450-8
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Liver Targeting and Improved Antiproliferative Effect of Doxorubicin Liposomes Modified with Galactosylated Lipid and PEG-Lipid

Abstract: Abstract. In this study, a cleavable PEG-lipid (methoxypolyethyleneglycol 2000-cholesteryl hemisuccinate, PEG 2000 -CHEMS) linked via ester bond and galactosylated lipid ((5-cholesten-3β-yl) 4-oxo-4-[2-(lactobionyl amido) ethylamido] butanoate, CHS-ED-LA) were used to modify doxorubicin (DOX) liposome. DOX was encapsulated into conventional liposomes (CL), galactosylated liposomes (modified with CHS-ED-LA, GalL), pegylated liposomes (modified with PEG 2000 -CHEMS, PEG-CL), and pegylated galactosylated liposome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It is a quite promising drug delivery system for cancer diagnosis and treatment in the future (Kuai et al, 2011). vinyl ether bond tumor interstitial fluid (pH 6.5-7.2); endosomes (pH 5.0-6.5) and lysosomes (pH 4.5-5.0) (Shin et al, 2003;Komeda et al, 2013) mPEG-b-P(ATMC-co- (Kale & Torchilin, 2007b;Prabaharan et al, 2009;Chen et al, 2010;Swati et al, 2011;Chen et al, 2012;Koren et al, 2012;Zhou et al, 2012;Sawant et al, 2012;Dong et al, 2013;Jiang et al, 2013;Koutroumanis et al, 2013;Quader et al, 2014;Wang et al, 2014a;Du et al, 2015) Hydrolyse ( (Ishida et al, 2001;Wang et al, 2010b;Chen et al, 2011;Hammer et al, 2014;Tang et al, 2014) Enzymolysis (MPP is expressed highly) (Zhang et al, 2...…”
Section: Disulfide Bond and Its Applicationmentioning
confidence: 99%
“…It is a quite promising drug delivery system for cancer diagnosis and treatment in the future (Kuai et al, 2011). vinyl ether bond tumor interstitial fluid (pH 6.5-7.2); endosomes (pH 5.0-6.5) and lysosomes (pH 4.5-5.0) (Shin et al, 2003;Komeda et al, 2013) mPEG-b-P(ATMC-co- (Kale & Torchilin, 2007b;Prabaharan et al, 2009;Chen et al, 2010;Swati et al, 2011;Chen et al, 2012;Koren et al, 2012;Zhou et al, 2012;Sawant et al, 2012;Dong et al, 2013;Jiang et al, 2013;Koutroumanis et al, 2013;Quader et al, 2014;Wang et al, 2014a;Du et al, 2015) Hydrolyse ( (Ishida et al, 2001;Wang et al, 2010b;Chen et al, 2011;Hammer et al, 2014;Tang et al, 2014) Enzymolysis (MPP is expressed highly) (Zhang et al, 2...…”
Section: Disulfide Bond and Its Applicationmentioning
confidence: 99%
“…The liver deals with most of the chemicals entering the body so, it is at high risk of damage. Hepatocytes are the main functional cells of the liver and constitute 60 ~ 80% of the mass of the liver tissue [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators reported that liposomes modified with galactosylated lipid could specifically deliver their contents to liver, elevate drug concentration in liver and promote anti-tumor effect [35], [36], [37], [38]. However, very few studies, to our knowledge, about their application in liver metastasis from primary tumors have been reported.…”
Section: Discussionmentioning
confidence: 99%